2018
DOI: 10.1155/2018/7914581
|View full text |Cite
|
Sign up to set email alerts
|

Multitemporal Soil Moisture Retrieval over Bare Agricultural Areas by Means of Alpha Model with Multisensor SAR Data

Abstract: e objective of this research is to optimize the Alpha approximation model for soil moisture retrieval using multitemporal SAR data. e Alpha model requires prior knowledge of soil moisture range to constrain soil moisture estimation. e solution of the Alpha model is an undetermined problem due to the fact that the number of observation equations is less than the number of unknown parameters. is research primarily focused on the optimization of Alpha model by employing multisensor and multitemporal SAR data. e d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Gao et al [27] proposed a capable soil moisture prediction model in the domain of change detection method through combining Sentinel-1 SAR and Sentinel-2 optical data, their validation lead to a RMSE equal to0.059 m 3 /m 3 . Alternatively, Zhang et al [28] introduced soil moisture estimation techniques using the Alpha approximation model and multi-temporal SAR data obtained from RADARSAT-2 and Senteinel-1 sensors, characterized by an RMSE of 0.08 cm 3 /cm 3 . While Hosseini et al [29] presented an integrated statistical soil moisture prediction model based on RADARSAT-2 data.…”
mentioning
confidence: 99%
“…Gao et al [27] proposed a capable soil moisture prediction model in the domain of change detection method through combining Sentinel-1 SAR and Sentinel-2 optical data, their validation lead to a RMSE equal to0.059 m 3 /m 3 . Alternatively, Zhang et al [28] introduced soil moisture estimation techniques using the Alpha approximation model and multi-temporal SAR data obtained from RADARSAT-2 and Senteinel-1 sensors, characterized by an RMSE of 0.08 cm 3 /cm 3 . While Hosseini et al [29] presented an integrated statistical soil moisture prediction model based on RADARSAT-2 data.…”
mentioning
confidence: 99%
“…The determination of these parameters by remote sensing is of interest, because surface roughness is one of the main sources of m v retrieval errors from satellite SAR sensors (Martinez-Agirre et al, 2017;Lievens et al, 2009). A number of strategies to eliminate surface roughness effects in the context of soil moisture retrieval from SAR were reviewed by McNairn and Brisco (2004), who discovered that to separate the effects of soil moisture and soil surface roughness requires diversity in measurement (Gorrab et al, 2016) comprising, multi-frequency (such as combining different SAR sensors (Zhang et al, 2018)), multi-angle (which might be achieved with different orbits of the same sensor (Wang et al, 2016)), or multi-polarisation. Mattia et al (1997) found that a co-polarised correlation coefficient based on circular polarisation is strongly correlated with surface roughness, but not soil moisture.…”
Section: Surface Roughnessmentioning
confidence: 99%
“…For example, JERS-1 SAR series images were used to analyze land use changes (Angelis et al 2002), and COSMO-Skymed data were used for land cover classification (Satalino et al 2011). Other works include an unsupervised change detection (Yousif and Ban 2015), a soil moisture retrieval (Zhang et al 2018), or the analysis of natural hazards (Poursanidis et al Poursanidis and Chrysoulakis 2017).…”
Section: Introductionmentioning
confidence: 99%